Determinants related to drug possession in households - Nailet Arraíz; Ayarí G. Ávila Larreal; Alberto E. Briceño García; Betty Benítez (Medwave, 2011)
Introduction: Drugs are used as therapeutic tools useful strategy to improve and maintain health. The use of drugs is a complex phenomenon that is influenced by several factors that are interesting to analyze. Objective: To identify determinants related to the possession of drugs in homes clustered in the socio-economic, personal and health system. Methods: A descriptive transversal to do so, applied 1092 surveys, April-July 2010. Sampling was intentional in the metropolitan area of the Municipality Trujillo, Trujillo State Venezuela. The instrument was structured in the following dimensions: 1) socio-economic, 2) personal, 3) health system. For data analysis, we applied chi square and binary logistic regression. Results: We found associations between number of drugs in the presence of patients at home (acute or chronic): odds ratio (OR): 2.5; p=0.000; 95% confidence interval (CI): 1,9-3,33; family income (measured in minimum wages): OR: 1.38; p=0.021; CI: 1.05-1.82 and the purchase of medications (prescription): OR: 2.5; p=0.000; 1,53 IC-4, 04. Conclusion: The variables that are correlated with increased number of drugs found in homes of patients were the presence of any type, higher family income and the purchase of medicines for families.